Retrospective, Demographic, and Clinical Investigation of the Causes of Postoperative Infection in Patients With Lumbar Spinal Stenosis Who Underwent Posterior Stabilization. Issue 29 (July 2015) - Yaldiz, Can; Yaldiz, Mahizer; Ceylan, Nehir; Kacira, Ozlem Kitiki; Ceylan, Davut; Kacira, Tibet; Kizilcay, Gokhan; Tanriverdi, Taner; Bernhard, Schaller.
<x xml:space="preserve">Abstract</x> Abstract Owing to the increasing population of elderly patients, a large number of patients with degenerative spondylosis are currently being surgically treated. Although basic measures for decreasing postoperative surgical infections (PSIs) are considered, it still remains among the leading causes of morbidity and mortality. The aim of this retrospective analysis is to present possible causes leading to PSI in patients who underwent surgery for lumbar degenerative spondylosis and highlight how it can be avoided to decrease morbidity and mortality. The study included 540 patients who underwent posterior stabilization due to degenerative lumbar stenosis between January 2013 and January 2014. The data before and after surgery was retrieved from the hospital charts. Patients with degenerative lumbar stenosis who were operated upon in this study had >2 levels of laminectomy and facetectomy. For this reason, posterior stabilization was performed for all the patients included in this study. Determining the causes of postoperative infection (PI) following spinal surgeries performed with instrumentation is a struggle. Seventeen different parameters that may be related to PI were evaluated in this study. The presence of systemic diseases, unknown glove perforations, and perioperative blood transfusions were among the parameters that increased the prevalence of PI. Alternatively, prolene sutures, double-layered gloves, and the use of rifampicin Sv (RIS) decreased the incidence of PI. Although the presence of systemic diseases, unnoticed glove perforations, and perioperative blood transfusions increased PIs, prolene suture material, double-layered gloves, and the use of RIS decreased PIs.